2018
DOI: 10.3390/cryst8050203
|View full text |Cite
|
Sign up to set email alerts
|

The Rietveld Refinement in the EXPO Software: A Powerful Tool at the End of the Elaborate Crystal Structure Solution Pathway

Abstract: The Rietveld method is the most reliable and powerful tool for refining crystal structure when powder diffraction data are available. It requires that the structure model to be adjusted is as close as possible to the true structure. The Rietveld method usually represents the final step of the powder solution process, in particular when a new structure is going to be determined and published. EXPO is a software able to execute all the steps of the solution process in a mostly automatic way, by starting from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…By refining the positions and lattice parameters we obtain the fitted curves for ZnS nanostructures given in Figure 2. The refined parameters R p (profile),R wp (weight profile) and R e -(expected) with regular convergence and least square(χ 2 ) gives the exact fitting [18] and these values are given in Table 1.…”
Section: Structural Analysismentioning
confidence: 99%
“…By refining the positions and lattice parameters we obtain the fitted curves for ZnS nanostructures given in Figure 2. The refined parameters R p (profile),R wp (weight profile) and R e -(expected) with regular convergence and least square(χ 2 ) gives the exact fitting [18] and these values are given in Table 1.…”
Section: Structural Analysismentioning
confidence: 99%
“…To identify the remaining content of the sample we fitted the CSD structure for pure THL and NIC to our cocrystals. This revealed the remaining amount to be uncrystallized Nicotinamide, however, the amount is minuscule at 1.5% and even less for the samples produced at 1.5 kg/hr at 0.9% [ 58 , 59 ]. From the results of this experiment, it can be concluded that the scale-up process had an insignificant effect on the purity of the cocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to the presence of the NIC coformer, with the more readily soluble NIC, assisting dissolution [ 61 ]. From this, it can be concluded that neither the cocrystallization process nor the scaling-up process had an adverse effect on the solubility of the theophylline [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A force convergence threshold of 1•10 −3 , mixing beta of .4, and automatic k points 1 2 2 0 0 0 were also used for all calculations. The theoretical calculations of UAM-1 were obtained using the fixed cell relaxation procedure starting from the indexed cell obtained by the EXPO14 Rietveld Refinement program suite (Altomare et al, 2018). The structural coordinates of half of the molecular entity were modified from the single-crystal X-ray structure experimentally obtained for Ag 2 BDC through the replacement of half BDC with half NDC ligands.…”
Section: Ft-irmentioning
confidence: 99%